2023
DOI: 10.21203/rs.3.rs-2506122/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Network analysis of pig movement data as an epidemiological tool: an Austrian case study

Abstract: Animal movements represent a major risk for the spread of infectious diseases in the domestic swine population. In this study, we adopted methods from social network analysis to explore pig trades in Austria. We used a dataset of daily records of swine movements covering the period 2015-2021. We analyzed the topology of the network and its structural changes over time, including seasonal and long-term variations in the pig production activities. Finally, we studied the temporal dynamics of the network communit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 81 publications
(138 reference statements)
1
5
0
Order By: Relevance
“…The dynamic network analysis revealed that the GSCC ranged from 0.2% to 2.59%, while the GWCC varied from 91.04% to 99.62%. These results highlight the extreme levels of verticalization of North American commercial swine production, as sows typically send weaned pigs to the same nurseries or wean-to-finisher premises and then to a wider range of finishers (Kinsley et al, 2019; Machado et al, 2019; Passafaro et al, 2020), similar patterns have also been described in Austria (Puspitarani et al, 2023) and Brazil (Cardenas et al, 2022, 2021). Time-independent, connected component sizes provide an overall estimation of the lower and upper bounds of epidemic sizes (Kao et al, 2006; Omondi et al, 2021); for the U.S., the upper bound estimates above 90% of premises are at risk of infection.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…The dynamic network analysis revealed that the GSCC ranged from 0.2% to 2.59%, while the GWCC varied from 91.04% to 99.62%. These results highlight the extreme levels of verticalization of North American commercial swine production, as sows typically send weaned pigs to the same nurseries or wean-to-finisher premises and then to a wider range of finishers (Kinsley et al, 2019; Machado et al, 2019; Passafaro et al, 2020), similar patterns have also been described in Austria (Puspitarani et al, 2023) and Brazil (Cardenas et al, 2022, 2021). Time-independent, connected component sizes provide an overall estimation of the lower and upper bounds of epidemic sizes (Kao et al, 2006; Omondi et al, 2021); for the U.S., the upper bound estimates above 90% of premises are at risk of infection.…”
Section: Discussionsupporting
confidence: 65%
“…An in-depth understanding of national movement patterns is a key element for epidemic control in highly integrated swine production systems. In the same vein, examining interstate and intrastate pig shipment data is crucial to informing national disease response plans, and developing novel tactics against endemic and emerging diseases (Cardenas et al, 2022; Hammami et al, 2022b; Puspitarani et al, 2023; Sykes et al, 2023). The median distance of pig shipment was 74 km, similar to what has been shown in other regional studies with shipment distances between 10 and 50 km (Kinsley et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, when stochastic network transmission models are used, information can be retrieved for early warning systems and to determine the spatial extent of the epidemic (5). Epidemic patterns depend on the interplay between the structure of the networks and the characteristics of the epidemic (6,7). The models’ assumptions, structure, complexity, and reliability depend on the data’s quality and degree of detail used to reconstruct the network and the information concerning the disease under study (4).…”
Section: Introductionmentioning
confidence: 99%